Menuju masyarakat cita : refleksi atas persoalan-persoalan kebangsaan - Majid, Nurcholish, 1939-; Himpunan Mahasiswa Islam (Indonesia). Badan Koordinasi (a [Ambon] : Badan Koordinasi Himpunan Mahasiswa Islam Maluku-Irian Jaya, 1997)
Essays reflecting on Indonesian politics, economics; collection of papers
Keywords: Himpunan Mahasiswa Islam (Indonesia); Islam -- Indonesia; Islam and state -- Indonesia; Indonesia -- Politics and government -- 1966-1998; Indonesia -- Economic conditions -- 1945-